Rethinking Islamophobia: A Transnational Crisis of Identity for the Potential Terrorist (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2024)
This paper explores the complex dynamics of Islamophobia as it relates to the construction of the “potential terrorist” identity. Islamophobia, driven by media narratives, political discourse, and global security concerns, often labels Muslims as inherent threats, reinforcing the stereotype of the “potential terrorist.” This stigmatization creates a transnational identity crisis for Muslims, particularly those who feel marginalized or alienated by society's perceptions. The paper critically examines how this identity crisis can push individuals towards radicalization by exacerbating feelings of isolation, distrust, and hostility toward systems that vilify them. By analyzing the historical roots of Islamophobia and the role of global events such as 9/11 and the subsequent “war on terror,” the paper argues that the branding of Muslims as potential terrorists is a socio-political construct. Drawing on scholarly insights, the paper underscores the need to rethink these narratives, as they fail to address the underlying causes of terrorism, such as political grievances, socio-economic disenfranchisement, and Western foreign interventions in the Muslim world. The paper further investigates how global policies, surveillance, and media portrayals reinforce the “potential terrorist” identity, often leading to discrimination, racial profiling, and even violent backlash against Muslim communities. In response, the paper advocates for a reevaluation of security discourses and calls for approaches that prioritize deconstructing Islamophobic stereotypes, promoting inclusivity, and addressing the legitimate grievances that may drive some individuals towards extremist ideologies.